Numerical methods in physics with Python / Alex Gezerlis. - Gezerlis, Alex (Cambridge University Press, 2023)
Combining idiomatic Python programming, foundational numerical methods, and physics applications, this book covers linear algebra, DEs, root-finding, interpolation, and integration. With full implementations of many numerical methods in Python, and more than 250 problems, this is an ideal standalone textbook for courses on computational physics.